Effectiveness of including weight management in smoking cessation treatments: A meta-analysis of behavioral interventions. (May 2023) - García-Fernández, Gloria; Krotter, Andrea; González-Roz, Alba; García-Pérez, Ángel; Secades-Villa, Roberto
Highlights: Addressing weight gain in treatments for smoking cessation improves quit rates. No additive effects of weight management after smoking treatment termination. Youth-friendly treatments are required to improve quitting among young adults. Abstract: Introduction: The potential of weight gain after smoking cessation reduces the incentive to quit. This meta-analysis examines the efficacy of behavioral interventions for smoking cessation that also address post-cessation weight gain. Methods: Medline, Web of Science, PsycINFO, and the Cochrane Central Register of Controlled Trials were searched for randomized controlled trials on behavioral treatments targeting both health outcomes. Six separate meta-analyses were undertaken to assess treatment efficacy on smoking abstinence and weight outcomes at end of treatment (EOT), short-term, and long-term follow-up. Individual and treatment moderators were examined as well as methodological quality and publication bias of studies. Results: A total of 28 studies were included in the meta-analysis. There was a statistically significant positive impact of treatments addressing both targets on smoking outcomes at EOT (RR = 1.279, 95% CI: 1.096, 1.492, p  = .002), but not at follow-ups. Age impacted on EOT abstinence rates Q (1) = 4.960, p  = .026) while increasing the number of sessions significantly improved EOT abstinence rates ( p  = .020). There was no statistically significant impact of these treatments on weight at EOT (Hedges' g  = −0.015, 95% CI: −.164, 0.135, p  = .849) or follow-ups (short term: Hedges' g  = 0.055, 95% CI: −0.060, 0.170, p  = .347; long term: Hedges' g  = −0.320, 95% CI: −.965, 0.325, p  = .331). There were minimal impacts of publication bias, mostly related to sample size, meaning studies including small sample sizes revealed larger effect sizes on abstinence at EOT. Discussion: Addressing post-cessation weight management in treatments for smoking cessation significantly enhances tobacco abstinence at EOT though it was not found to have a lasting impact after treatment.